Application of abscisic acid and 6-benzylaminopurine modulated morpho-physiological and antioxidative defense responses of tomato (Solanum lycopersicum L.) by minimizing cobalt uptake. (January 2021) - Kamran, Muhammad; Danish, Mohammad; Saleem, Muhammad Hamzah; Malik, Zaffar; Parveen, Aasma; Abbasi, Ghulam Hassan; Jamil, Moazzam; Ali, Shafaqat; Afzal, Sobia; Riaz, Muhammad; Rizwan, Muhammad; Ali, Muhammad; et al.
Abstract: A hydroponic study was conducted to determine the effects of single and/or combined application of different doses (0, 5 and 10 μM L −1 ) of abscisic acid (ABA) and 6-benzylaminopurine (BAP) on cobalt (Co) accumulation, morpho-physiological and antioxidative defense attributes of tomato ( Solanum lycopersicum L.) exposed to severe Co stress (400 μM L −1 ). The single Co treatment (T1), prominently decreased tomato growth, relative water contents, photosynthetic pigments (chlorophyll a and chlorophyll b ), whereas enhanced oxidative stress and Co accumulation in shoot and root tissues. Nonetheless, the supplementation of ABA and 6-BAP via nutrient media significantly ( P < 0.05) enhanced plant biomass, root morphology and chlorophyll contents of tomato, compared to only Co treatment (T1). Moreover, the oxidative stress indicators such as malondialdehyde, proline and H2 O2 contents were ameliorated through activation of enzymatic antioxidant activities i.e. ascorbate peroxidase, superoxide dismutase, catalase, and peroxidase, in growth modulator treatments in comparison to T1. The Co uptake, translocation (TF) and bioaccumulation factor (BAF) by shoot and root tissues of tomato were significantly reduced under all the treatments than that of T1. The supply of 6-BAP alone or in combination with ABA at 10 μM L −1 application (T7) rate was found the most effective to reduce Co accumulation in the roots and shoots by 48.4% and 70.2% respectively than T1 treatment. It can be concluded that two plant growth modulators could improve the stress tolerance by inhibition of Co uptake in tomato plants. Highlights: Cobalt (Co 2+ ) stress reduced tomato growth, increased oxidative stress and Co accumulation. Plant growth modulators (PGMs) supply increased plant biomass by alleviating Co-induced phytotoxicity. PGMs application reduced Co uptake, translocation and consequently, bioaccumulation. 6-benzylaminopurine (6-BAP) alone and/or combined with abscisic acid (ABA) showed better effects than ABA alone.